Quality of life related to health and its relation in patients with diagnostic of slight arterial hypertension - Vinaccia, Stefano; Universidad de San Buenaventura, Medellín, Colombia (Universidad Santo Tomás, Colombia, 2007)
The purpose of this investigation was to evaluate the extent of quality of life related to health in 282 patients with slight arterial hypertension from the city of Medellin, Colombia. The questionnaire Quality of Life Hypertension (CHAL) was used. The results demonstrated an important deterioration in the quality of life of these patients at level of the state mind and mainly in his somatic manifestations. Key words: Quality of life, health, slight arterial hypertension, symptoms.